IMPACT OF A BEHAVIORAL INTERVENTION ON DIET, EATING PATTERNS, SELF-EFFICACY, AND SOCIAL SUPPORT: TEXERCISE SELECT. (11th November 2018) - Smith, M; Lee, S; Towne, S; Han, G; Quinn, C; Pena-Purcell, N; Ory, M
Abstract: Poor dietary patterns are associated with preventable chronic conditions and health consequences among older adults living with comorbid conditions. Given the multi-level influences on diet, multi-factorial interventions are needed to improve healthy eating. This study examined the effectiveness of a structured multi-modal behavioral intervention to change dietary behaviors as well as self-efficacy and social support for engaging in healthier diets. Participants were recruited by community organizations from 2015–2017. Quasi-experimental methods were used to assign sites into intervention and comparison (no intervention) groups. Data were collected at baseline, 3 months, and 6 months. Intervention group participants enrolled in Texercise Select, a 12-week lifestyle enhancement program offered in a small group education format. Multiple mixed-effects models were used to examine nutrition-related changes over time. Subgroup analyses were performed to assess the intervention impact on those with cardiovascular risk at baseline. For the intervention group, significant improvements were observed for fast food consumption (p=0.011), fruit/vegetable consumption (p=0.008), water consumption (p=0.009), and social support (p<0.001) from baseline to 3 months. The same outcomes were observed among the intervention group with cardiovascular risk, although self-efficacy to engage in a healthy diet (p=0.037) also emerged as significant. Intervention group improvements at 3 months were significantly greater than those for the comparison group. Texercise Select is an effective program to improve diet-related outcomes. Strong effects among those with cardiovascular risk suggest they are especially well-suited for this intervention and highlight the need for strategic community partnerships to recruit at-risk participants with conditions like heart disease and diabetes.